The relationship of financial leverage and profitability: evidence from Malaysia companies / Dg Ku Nur Liyana Amalina Kipli - Kipli, Dg Ku Nur Liyana Amalina (2019)
Capital structure is a combination of two components of debt and equity used by a company to fund its activities. The decision on capital structure is essential because it requires maximizing firm returns, and the effect of this choice allows companies to cope with their competitive setting and financial leverage benefit the company make a better return on their assets. Hence, this study will examine the relationship between financial leverage and profitability of Malaysian companies. Sample of 54 firm from 100 top companies by market capitalization that listed in Bursa Malaysia use in this research paper. Moreover, 54 companies are the total number that have complete variable data used in this study. This study use ROE as measurement of profitability and long-term debt, short-term debt and total debt as proxies for financial leverage. Thus, the research indicated that between total debt and profitability there is a positive association, but having lower significant levels implies that some profitable firms may use debt financing as their external financing to obtain a better return for their business.